Child Maltreatment in Residential Care History, Research, and Current Practice - Rus, Adrian V.; Parris, Sheri R.; Stativa, Ecaterina (Cham Springer International Publishing, 2017)
This data-rich volume reviews short- and long-term consequences of residential or institutional care for children across the globe as well as approaches to reducing maltreatment. Up-to-date findings from a wide range of developing and developed countries identify forms of abuse and neglect associated with institutionalization and their effects on development and pathology in younger children, adolescents, and alumni. The sections on intervention strategies highlight the often-conflicting objectives facing professionals and policymakers balancing the interests of children, families, and facilities. But despite many national and regional variations, two themes stand out: the universal right of children to live in safety, and the ongoing need for professionals and community to ensure this safety. Included among the topics: Maltreatment and living conditions in long-term residential institutions for children Outcomes from institutional rearing Recommendations to improve institutional living Historical, political, socio-economic, and cultural influences on Child Welfare Systems Latin American and the Caribbean, African, Asian, Middle-Eastern, Western and Eastern European countries and the United States of America are presented. Child Maltreatment in Residential Care will inform psychology professionals interested in the role of residential care in the lives of children, and possibilities for improved outcomes. It will also interest social workers and mental health practitioners and researchers seeking evidence-based interventions for families adopting children from residential care
Keywords: Public health; School psychology; Child psychology; Social Work; Child and School Psychology; Social work; Public Health